2020
DOI: 10.15390/eb.2020.7765
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Inquiry Learning Skills towards Math of Middle School Students in terms of Inquiring, Evaluating, Reasoning, and Reflective-Thinking Skills for Problem-Solving

Abstract: Araştırmada, ortaokul öğrencilerinin matematiğe yönelik sorgulayıcı öğrenme beceri algılarını belirlemek amacıyla bir ölçeğin geliştirilmesi, geliştirilen ölçeğin sınanması ve matematiğe yönelik sorgulayıcı öğrenme becerilerinin problem çözmeye yönelik sorgulama, değerlendirme, nedenleme ve yansıtıcı düşünme becerileri açısından değerlendirilmesi amaçlanmıştır. Bu amaçla çalışma iki aşamada gerçekleştirilmiştir. İlk aşamada ölçeğin geçerlik ve güvenirliği araştırılarak kullanılabilirliği ortaya konmuştur. İkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The lack of difference in the post-tests of the experimental and control groups may be since the textbook activities applied in the control group also focused on developing reflective thinking. Recently updated teaching programs at our schools positively affect students to acquire reflective thinking skills and inquiry learning (Katrancı & Şengül, 2020). This finding was in line with the study results (Dadlı, 2017), which examined the effect of authentic PBL activities on secondary school students' RTS.…”
Section: The Results and Discussion For The Third Research Questionsupporting
confidence: 87%
See 2 more Smart Citations
“…The lack of difference in the post-tests of the experimental and control groups may be since the textbook activities applied in the control group also focused on developing reflective thinking. Recently updated teaching programs at our schools positively affect students to acquire reflective thinking skills and inquiry learning (Katrancı & Şengül, 2020). This finding was in line with the study results (Dadlı, 2017), which examined the effect of authentic PBL activities on secondary school students' RTS.…”
Section: The Results and Discussion For The Third Research Questionsupporting
confidence: 87%
“…When the relationship between ILS scores and RTS for the problem-solving scores in Table 12 over the pre-test and post-test total scores of the students is examined, it is seen that there is a moderately significant positive relationship between them. Similarly, a moderate positive correlation was found between middle school students' inquiry learning skills and reflective thinking skills for problemsolving (Katrancı & Şengül, 2020). In a different study, a positive, significant, and moderate relationship was found between pre-service teachers' critical thinking and reflective thinking skills (Aşkın-Tekkol & Bozdemir, 2018;Erdoğan, 2020).…”
Section: The Results and Discussion For The Sixth Research Questionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to Demirel, Derman and Karagedik (2015) and Kızılkaya and Aşkar (2009) the level of reflective thinking skills for problem solving of secondary school students were not sufficient. Katrancı and Şengül (2020) also determined the questioning skills of secondary school students at an intermediate level. In the research of Aydın and Diker Coşkun (2016), it was found that the eighth grade students' reflective thinking skills for problem solving were low.…”
Section: Resultsmentioning
confidence: 99%
“…Rani (2006) found in his research that achievement motivation was found to have statistically significant effects on science attitudes only in the eighth grade and the ninth grade. Katrancı and Şengül (2020) determined that the success levels of secondary school students positively affected their inquiry skills towards mathematics. In the study of İnel Ekici (2017), it was stated that students who have high scientific inquiry skills have higher level of participation, interest and attention in the learning process, and so their success increased because of the effect of these variables.…”
Section: Resultsmentioning
confidence: 99%